Application of MRI Post-processing in Presurgical Evaluation of Non-lesional Cingulate Epilepsy - Wang, Shan; Jin, Bo; Aung, Thandar; Katagiri, Masaya; Jones, Stephen E.; Krishnan, Balu; Gonzalez-Martinez, Jorge A.; Prayson, Richard A.; Najm, Imad M.; Alexopoulos, Andreas V.; Wang, Shuang; Ding, Meiping; et al. (Frontiers in Neurology, 2018)
Background and purpose: Surgical management of patients with cingulate epilepsy (CE) is highly challenging, especially when the MRI is nonlesional. We aimed to use a voxel-based MRI post-processing technique, implemented in a morphometric analysis program (MAP), to facilitate detection of subtle epileptogenic lesions in CE, thereby improving surgical evaluation of patients with CE with nonlesional MRI by visual inspection. Methods: Included in this retrospective study were 9 patients with CE (6 with negative MRI and 3 with subtly lesional MRI) who underwent surgery and became seizure-free or had marked seizure improvement with at least 1-year follow-up. MRI post-processing was applied to pre-surgical T1-weighted volumetric sequence using MAP, which was then co-registered with other imaging modalities. Patients were further studied in terms of their presurgical evaluation tests and surgical pathology. Results: Single MAP+ abnormalities were found in 6 patients, including 3 patients with negative MRI and 3 patients with subtly lesional MRI. Out of these 6 MAP+ patients, 4 patients became seizure-free after complete resection of the MAP+ abnormalities; 2 patients didn’t become seizure-free following laser ablation that only partially overlapped with the MAP+ abnormalities. All MAP+ foci were concordant with intracranial EEG when performed. The localization value of FDG-PET, SPECT and MEG was limited. FCD was identified in all patients’ surgical pathology except for two cases of laser ablation with no tissue available. Conclusion: MAP provided helpful information for identifying subtle epileptogenic abnormalities in patients with nonlesional cingulate epilepsy. MRI postprocessing should be considered to add to the presurgical evaluation test battery of nonlesional cingulate epilepsy.